Overstorey evapotranspiration in a seasonally dry Mediterranean eucalypt forest: Response to groundwater and mining. Issue 5 (6th April 2018) - Macfarlane, Craig; Grigg, Andrew; McGregor, Rod; Ogden, Gary; Silberstein, Richard
Abstract: Groundwater levels in the northern jarrah forest have declined at rates up to 0.5 m year −1 owing to increased aridity in south‐western Australia in the last 40 years. The forest has also been mined and rehabilitated resulting in significant areas of postmining forest. We tested the impact of declining groundwater levels and mining on evapotranspiration by jarrah forest overstorey. We hypothesized that trees in jarrah forest are facultative phreatophytes (will use groundwater where available but are not reliant on it) and water use per unit overstorey leaf area index ( L os ) of postmining forest is the same as that of postharvest forest. We measured sapflow at 7 sites in the northern jarrah forest and measured rainfall interception by the canopy at 9 sites. Stemflow was measured at 3 sites. Shallow depth to groundwater was associated with a larger ratio of transpiration per unit leaf area ( E os / L os ), but there was little difference in E os / L os between postmining and postharvest jarrah forest. E os / L os ranged from 250 ‐ 340 mm year −1 (m 2  m −2 ) −1 at sites where depth to groundwater was >15 m but was up to 400–500 mm year −1 (m 2  m −2 ) −1 at some sites with shallow groundwater. Based on relationships between transpiration, rainfall interception, and L os, it is possible to estimate overstorey evapotranspiration in jarrah forest from L os, especially if spatial layers are available for depth to groundwater. We conclude that jarrah forest is conservative in its water use and likely to be resilient to a drying climate. Management implications for the northern jarrah forest are briefly discussed.